Assuming the role of mitochondria in mycobacterial infection. Issue 4 (December 2016) - Dubey, Rikesh K.
Abstract: Tuberculosis is one of the leading causes of death by Mycobacterium tuberculosis ( Mtb ) affecting millions of people worldwide. Mycobacterium species enter host macrophages during infection and target various cellular organelles and their function for their own benefit. Mitochondria appear to be among the important targets for bacterial pathogens. Mtb and other pathogenic bacteria secrete various proteins that initiate structural changes in mitochondria to modulate its function. Additionally, virulent mycobacteria interfere with the balance between pro- and anti-apoptotic factors to inhibit apoptosis and, in later stages, promote necrosis. Furthermore, mitochondria perform multiple biological functions in the cell, and the inhibition of these functions by bacterial proteins promotes Mtb survival, growth, and successful infection.